2023
DOI: 10.3390/su152316386
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Innovation Ecosystem Development: Bibliometric Review of Scopus Database

Lina Pilelienė,
Giedrius Jucevičius

Abstract: The paper focuses on the bibliometric review of the Scopus database in the field of innovation ecosystem development, aiming to reveal the key trends in this fast-growing area of interdisciplinary research in terms of different quantitative and qualitative parameters. The bibliometric analysis followed PRISMA protocol guidelines for finding and extracting relevant scholarly papers based on the selected national, institutional, demographic, and scientific variables. The PRISMA procedure resulted in 401 selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…As it has been noted above, research into the directions of innovative development of rural green tourism in Ukraine is fragmentary; therefore, based on the results of existing publications on this topic [6], the current state of development of the industry was analyzed, identifying trends and determining the main directions of its innovative development, taking into account global, national, and regional trends.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been noted above, research into the directions of innovative development of rural green tourism in Ukraine is fragmentary; therefore, based on the results of existing publications on this topic [6], the current state of development of the industry was analyzed, identifying trends and determining the main directions of its innovative development, taking into account global, national, and regional trends.…”
Section: Discussionmentioning
confidence: 99%
“…A review of scientific articles published on the topic of using innovations for sustainable economic development, circular economy, smart tourism destinations, and innovative ecosystems in the Scopus database during the last decade showed that this field of research is at the nascent stage [6]; therefore, conducting interdisciplinary research and focusing on the introduction of innovations in a certain industry is currently relevant.…”
Section: Literature Review 21 Innovative Directions Of Rural Green To...mentioning
confidence: 99%
See 1 more Smart Citation
“…To encourage more Lithuanians to come to Poland for shopping, better transportation possibilities can be offered as they positively affect cross-border exchanges. Also, recent research indicated the necessity of the symbiosis of research in the fields of entrepreneurship, digitalization, smart environments, and sustainability [52], thus emphasizing the possible future changes in the role of regional factors through various forms of e-commerce.…”
Section: Discussionmentioning
confidence: 99%
“…The development of innovation ecosystem is the object of research by scientists from the Vytautas Magnus University. In their article (Pilelienė & Jucevičius, 2023), the authors made a bibliometric review of the Scopus database in the field of innovation ecosystem development in order to identify key trends in this rapidly growing field of interdisciplinary research by various quantitative and qualitative parameters. Key findings indicate that research on innovation ecosystem development began to develop late, which is a sign that this area is still understudied.…”
Section: Literature Reviewmentioning
confidence: 99%